Faktor-Faktor yang dapat Mempengaruhi Nilai Impor Provinsi Bali - Abdurahman, Alief Muhammad; Kesuma Jaya, I Wayan Wita (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 5, No. 6, Juni 2016 (pp. 652-728), 2016)
Import Indonesia can not be separated from the influence of domestic demand on consumer and the import of raw and auxiliary materials. Imports in Bali each year has fluctuated, it was caused by several factors such as income per capita, US dollar exchange rate and inflation fluctuates. The purpose of this study is to see the effect of variable income per capita, US dollar exchange rate and inflation against imports in the period from 1994 to 2013 in Bali Province. This study uses secondary data with multiple regression analysis. Based on the analysis found income Percapita has positive and significant effect , exchange rate US dollar, and inflation have significant effect on imports in Bali, partially income percapita income positive and significant positive effect, exchange rate US dollar negative and significant effect. But inflation has no significant effect on imports in Bali Province.Related with the import of Bali Province government is expected to be more concerned about the quality and usefulness of imports.
Keywords: Income percapita, exchange rate of U.s. Dollar, inflation, impor